Turismo accesible para personas con discapacidad física en los atractivos turísticos de la “Ruta turística del pueblo mágico de Saraguro - Ordoñez Fierro, Leyde Silvana (2024)
Saraguro is one of the cantons with tourist potential where its economy is based mainly on agriculture, livestock and tourism. Taking into account its characteristic of being a Magical Town, it was proposed to enhance this quality to extend its tourist character towards inclusivity. The general objective of the research was to establish a proposal for accessible tourism for people with physical disabilities in the tourist attractions of the “Ruta turística del pueblo mágico de Saraguro”: likewise, 2 specific objectives were proposed: Diagnose the accessibility facilities for people with physical disabilities in the tourist attractions of the “Ruta turística del pueblo mágico de Saraguro”, for which the environment was described, through a site profile of the canton, an analysis of the tourist plant of accessible tourist services, updating the inventory of attractions through summary sheets, determining the accessibility of the attractions through the MINTUR accessibility sheet; An interview was conducted to determine the criteria of the entities involved, and a survey was conducted to determine the potential demand. Among the results obtained, it was determined that the Ruta turística del pueblo mágico de Saraguro has nine natural and cultural tourist attractions that do not have adequate accessibility, also, there is a low percentage of accessible tourist plant. The second objective is to propose inclusive tourism strategies for people with physical disabilities in the tourist attractions of the “Ruta turística del pueblo mágico de Saraguro”, Strategies were proposed through the use of cards prepared by the author so that they could be implemented in the attractions in the future. It can be concluded that the tourist route has several natural and cultural attractions, which lack improvement plans and accessible tourism development. The strategies to be implemented are determined by: Training on accessible tourism and associativity, design a proposal for infrastructure and inclusive tourism signage for the attractions, and finally propose the certification of accessible destination to the tourist route of the magical town of Saraguro.